Picady2: A computer program to predict capacities, queues, and delays - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
ABSTRAK PICADY2 is a computer program which predicts capacities, queues and delays at major/minor priority junctions. This program has been developed by MVA Systematica under contract to Road Research Laboratory, Department of Transport, United Kingdom. The capacities were predicted using formulae developed by Kimber and Coombe (1980) which derived empirically the stream capacities as explicit functions of the controlling major road flows and the junction geometric features. The associated queues and delays were predicted using an approximation method developed by Kimber and Hollis (1979). Keywords: PICADY, stream capacity